2001
DOI: 10.1108/02656710110364477
|View full text |Cite
|
Sign up to set email alerts
|

ISO 9000 series ‐ Certification and performance

Abstract: In this article, the relationship is studied between certification on the ISO 9000 series and the performance of organizations. It is often claimed that ISO certification generates an improvement in the performance of organizations. This research aims to find out if ISO certification indeed results in better performance outcomes for organizations. This is of importance, for example, for those organizations that seek ISO certification in order to improve their performances. To test the hypothesis, an instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
246
0
30

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(293 citation statements)
references
References 10 publications
(32 reference statements)
17
246
0
30
Order By: Relevance
“…Empirical work supports the positive direct link between quality performance and firm profitability (Flynn et al, 1994(Flynn et al, , 1995aSingles et al, 2001;Tsekouras et al, 2002;Wayhan et al, 2002;Kaynak, 2003;Maiga et al, 2013). For example, Tatikonda and Montoya-Weiss (2001) find that product quality does, in fact, translate into financial performance.…”
Section: Quality Performance and Firm Profitabilitymentioning
confidence: 90%
“…Empirical work supports the positive direct link between quality performance and firm profitability (Flynn et al, 1994(Flynn et al, , 1995aSingles et al, 2001;Tsekouras et al, 2002;Wayhan et al, 2002;Kaynak, 2003;Maiga et al, 2013). For example, Tatikonda and Montoya-Weiss (2001) find that product quality does, in fact, translate into financial performance.…”
Section: Quality Performance and Firm Profitabilitymentioning
confidence: 90%
“…We mean by external environment all those elements outside an organization that have potential to affect all or part of it (like customers, competitors, government and suppliers). Carlsson and Carlsson (1996), Escanciano et al (2001) 2000; Tsekouras et al, 2002;Wayhan et al, 2002) or qualitative performances (Arauz and Suziki, 2004;Brown et al, 1998;Bryde and Slocock, 1998;Buttle, 1997;Chow-Chua et al, 2003;Escanciano et al, 2001;Huarng et al, 1999;Jones et al, 1997;Singels et al, 2001). For example (Buttle, 1997) found that "improving efficiency", "improving awareness of procedural problems" and "better management control" were the top three benefits perceived by the firms studied, followed by "using standard as a promotional tool" and "increasing customer satisfaction".…”
Section: Introductionmentioning
confidence: 99%
“…It can have: a) internal effects through processes (increase of workers and infrastructure productivity, improvement of efficiency, reduction of costs), and b) external effects through the market (related to the effect of quality on customers satisfaction and on services demand; increase of sales and market share, improvement of image, etc. (SINGELS; RUËL; VAN DE WATER, 2001).…”
Section: Relation Between the Tqm And The Business Resultsmentioning
confidence: 99%